SURVEY OF THE ASSESSMENT PROCESS OF PHYSICAL EDUCATION LEARNING DURING THE COVID-19 PANDEMIC AT TANJUNGBALAI STATE HIGH SCHOOLS - Nasution, Syafriza Alwie; Nasution, Usman (Universitas Negeri Medan, 2023)
Teacher assessment results in authentic assessment as the implementation of the 2013 curriculum in public high schools throughout the city of Tanjungbalai. This goal will result in the achievement of teacher performance in the learning process. This type of research is field research. The method that will be used in this research is to use quantitative research methods, with the data collection method used is a questionnaire (questionnaire). Based on the results of the study, it was concluded that the PJOK learning assessment process during the COVID-19 pandemic in public high schools throughout the city of Tanjungbalai in 2020/2021 showed results with a percentage of 78.52%. In the indicator of the process of preparing the test 78.23%, the process of taking the value of 78.62% and the process of determining the criteria for the value of 78.70%. Based on the results of the study, as a material for improvement in the implementation of the 2013 curriculum, the suggestions that can be given are that teachers should make a detailed and thorough assessment plan so that no points in the indicators are missed in the assessment. So that it meets the authentic assessment criteria and is in accordance with the 2013 curriculum standards.